Program Gerakan Literasi Sekolah di SD Negeri Sidomulyo 2 Demak Semester Ganjil Tahun 2021/2022 - Ayu Tri Ambarwati; Joko Sulianto; Mira Azizah (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to describe the implementation of GLS at SDN Sidomulyo 2 Demak. The research was conducted at SDN Sidomulyo 2 Demak, in class III and IV with 10 students. This research uses a descriptive qualitative method. The research subjects were principals, teachers, students grades III and IV. Data collection techniques using data triangulation, namely questionnaires, interviews and documentation. The results showed the GLS at SDN Sidomulyo 2 Demak was running well, it was known from the observations made in grades I to VI and the distribution of questionnaires in grades III and IV. GLS at SDN Sidomulyo 2 Demak has good with average score of 80.00%, for facilities and infrastructure has been used very well with a score 85.00% for participation of students in reading habituation activities is very good with a score 85.10%. In the habit of reading 15 minutes before learning at this time in the habituation stage. Teachers still take part in GLS implementation activities. Based on the results of this study, the conclusion are the success of GLS activities can be through reading activities as well as facilities and infrastructure that can foster student interest in the process of habituation of 15 minutes of reading before learning.